Pathways to mental health care in KwaZulu - Natal - L.P. Mkize; L.R. Uys (AOSIS, 2004)
The understanding of popular beliefs about mental health care and the pathways clients take prior to admission to a mental health institution is vital in planning to reduce delays in seeking treatment. The objectives of this exploratory survey were to determine pathways of care the clients with mental illness take, which ultimately lead to the mental health institution, the effects of socio-cultural and economic factor on the pathways to mental health care and the satisfaction with different service providers consulted. Data was gathered through semi-structured interviews. The results indicate that African clients interpret mental illness as bewitchment. Delays in seeking appropriate mental health care are experienced because traditional and faith healers are the first port of call. The short pathways are used when the first signs of psychotic features are severe, including like aggressive or violent behaviour. Financial constraints seem to be the problem for most of the clients in accessing mental health care. Furthermore, defaulting treatment was also observed due to the fact that mental illnesses are stigmatised in African communities.